Near-Fatal Asthma With Severe Hypercapnic Respiratory Failure Requiring Mechanical Ventilation In A Resource-Limited Setting: A Case Report - Sinta Triagustina; Delta Iswara; Anggita Dian Karera; Rois Hasyim; Rachmad Aji Saksana (International Journal of Health Engineering and Technology, 2026)
Near-fatal asthma (NFA) is a life-threatening manifestation of acute severe asthma characterized by hypercapnia, respiratory acidosis, altered consciousness, and the need for invasive mechanical ventilation. Early recognition and timely airway stabilization are essential to prevent respiratory arrest and mortality, particularly in resource-limited settings. A 41-year-old woman with a history of asthma was brought to the emergency department with decreased consciousness and severe respiratory distress. On arrival, her Glasgow Coma Scale score was 5, respiratory rate was 35 breaths per minute, and oxygen saturation was 46% on room air. Arterial blood gas analysis demonstrated life-threatening hypercapnic respiratory failure (pH 6.954; PaCO₂ 95.4 mmHg; P/F ratio 87). Due to worsening respiratory failure and decreased level of consciousness, the patient underwent immediate endotracheal intubation and invasive mechanical ventilation and was admitted to the intensive care unit. She received systemic corticosteroids, repeated bronchodilator therapy, aminophylline infusion, and broad-spectrum antibiotics. Lung-protective ventilatory strategies with prolonged expiratory time were applied. The patient improved rapidly and was successfully extubated on the second day of mechanical ventilation, with subsequent discharge in stable condition. Appropriate ventilatory strategies combined with guideline-based pharmacological therapy are essential to improve outcomes in patients with near-fatal asthma presenting with severe hypercapnic respiratory failure, even in resource-limited settings.